Antibacterial and antioxidant properties of selected Yemeni stones: potential for safe and cost-effective therapeutic applications - Wafa M. Al-Madhagi; Mohammed A. Alkhawlani; Majed Alwan; Maged Al-Najar (Discover Applied Sciences)
Abstract Background Yemen's diverse geological environment offers a variety of stone types that may possess significant medical benefits. In particular, some Yemeni stones have demonstrated antimicrobial and antioxidant activities, suggesting their potential for use in developing cost-effective antibacterial agents. Objective This study aimed to evaluate the antimicrobial and antioxidant properties of selected Yemeni stone powders and assess their potential as effective, and inexpensive antibacterial agents. Methodology Stone samples were collected from different regions of Yemen between September 2022 and November 2022. The antimicrobial activity was assessed using well diffusion assays, followed by determination of the minimum inhibitory concentration (MIC) and minimum bactericidal/fungicidal concentration (MBC/MFC) via serial dilution techniques. Two extraction solvents (DMSO and ethanol) were used, and results were expressed as mean ± SEM. Antioxidant activity was evaluated using the DPPH radical scavenging assay, with vitamin C serving as the positive control. Results The Yemeni stone powders exhibited variable biological activity. For extracts dissolved in DMSO, Tuff (Sample 1) showed strong broad-spectrum antimicrobial activity with MIC values ranging from 0.16 ± 0.00 mg/mL for Pseudomonas aeruginosa to 0.47 ± 0.03 mg/mL for Escherichia coli and MRSA, while Kaolin (Sample 13) demonstrated the strongest antimicrobial effect with an MIC of 0.424 mg/mL and an MBC of 0.683 mg/mL. In antioxidant assays, Orthoclase (Sample 2) exhibited the most potent free radical scavenging ability with an IC₅₀ of 23.08 ± 0.78 mg/100 µL, approaching the efficacy of vitamin C (IC₅₀ = 13.93 ± 1.12 mg/100 µL). Other stone samples, including Hematite, Limestone, Quartz, Marble, and Fluorite, displayed moderate activity, with MIC values between 0.1563 mg/mL and 0.683 mg/mL and antioxidant IC₅₀ values ranging from 36.03 ± 1.44 mg/100 µL to 80.29 ± 0.79 mg/100 µL. Conclusions The findings indicate that certain Yemeni stone powders, particularly Kaolin (Sample 13) and Orthoclase (Sample 2), possess promising antimicrobial and antioxidant properties. The strong antibacterial activity (e.g., an MIC of 0.424 mg/mL for Kaolin) and potent antioxidant activity (IC₅₀ of 23.08 ± 0.78 mg/100 µL for Orthoclase) suggest that these stones could serve as natural, cost-effective sources for developing new antibacterial agents.